2016
DOI: 10.1177/2396987316674085
|View full text |Cite
|
Sign up to set email alerts
|

A role for autophagy in carotid atherosclerosis

Abstract: Purpose: Autophagy has emerged in recent years as a critical cellular survival mechanism for cell homeostasis and may play a protective role in atherosclerosis. We aimed to review here the role autophagy plays in different cell types present in carotid atherosclerotic plaques and that may be associated with the development of unstable carotid atheroma plaque. Methods: We performed a thorough literature exploration in this area of research covering the three main cell types present in carotid atheroma plaques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“… 32 Autophagy has emerged in recent years as a critical cellular survival mechanism for cell homeostasis and may play a protective role in atherosclerosis. 33 Autophagy-related biomarkers have been found in many atherosclerotic diseases, including hsa_circ_0030042 in coronary arteries, Beclin 1 in major intracranial artery, DR-NPs in the abdominal artery and miR-100 in aorta. However, there are few autophagy-related studies, comparing early carotid atherosclerosis with advanced carotid atherosclerosis samples.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Autophagy has emerged in recent years as a critical cellular survival mechanism for cell homeostasis and may play a protective role in atherosclerosis. 33 Autophagy-related biomarkers have been found in many atherosclerotic diseases, including hsa_circ_0030042 in coronary arteries, Beclin 1 in major intracranial artery, DR-NPs in the abdominal artery and miR-100 in aorta. However, there are few autophagy-related studies, comparing early carotid atherosclerosis with advanced carotid atherosclerosis samples.…”
Section: Discussionmentioning
confidence: 99%
“…The most important upstream regulators of autophagy are AMPK and mammalian target of rapamycin. Moreover, some studies have found that AMPK and mammalian target of rapamycin interact with each other 44 , 45 . From autophagosomes to autolysosomes, autophagy-related proteins such as Atg5, Atg7, LC3II, and p62 are indispensable for the occurrence and development of autophagy 46 .…”
Section: Discussionmentioning
confidence: 99%
“…ATG5 then bounds to ATG16 and facilitates cytoplasmic proteins delivery to lysosomes for degradation [26]. Along with MAPLC3B, ATG12-ATG5-ATG16 complex elongates the phagophore membrane and dissociates when autophagosome formation is complete [27]. We found that the conjugated ATG5-ATG12 complex was up regulated in LSCD-diseased corneal epithelial cells.…”
Section: Discussionmentioning
confidence: 74%